Monotonic behaviour of beam-to-column connections with double channel cold-formed steel sections - Tan, Boon Kai (2014)
Cold-formed steel is a lightweight construction material generally in C or Z shaped produced by cold rolling from strip steel. It can be applied in the Industrialized Building System (IBS) in order to reduce the time and cost in construction project. Partial strength connection is a connection whereby the moment resistance of the connection is less than that of the moment capacity of the connected beam. In this paper, Numerical simulation is conducted by using ANSYS Workbench 14.0 in order to predict the structural behaviors of cold formed steel partial strength connection. The objective of this study is to develop moment rotation curve for flange-web-cleat connection using double channel cold formed steel section under monotonic loading. Experiment test results are then used to compare and validate the results from the finite element modeling. This study aims to understand the behaviour of cold-formed steel connections under monotonic loading. The beam section of 1.5-meter length and column of 3-meter length is modeled in this study. Three different beam depth have been selected in this study, which is 150mm, and the depth of column section is fix to 250mm. Brackets connections were chosen and all connections were formed using bolts. The monotonic load is applied at 1000mm from the column surface. The stiffness and moment capacity is obtained from the moment rotation curve which plotted from the modeling results. As a conclusion, The FEM initial results showed good agreement with experimental results.